Єврейські громади Таврійської губернії в революції 1917 року: суспільно-політичні аспекти діяльності (за матеріалами сімферопольської газети "Южные ведомости") - Вінцковський, Т. (Краєзнавство, 2021)
Мета дослідження полягає у необхідності вивчити участь єврейських громад Таврійської губернії (за винятком Сімферополя) у суспільно-політичному житті краю в період революції
1917 р. як елементу комплексу етнополітичних студій у визначеному напрямку. Методологія дослідження визначається вибором загальнонаукових методів, зокрема аналітичного і синтетичного, методу описування й загальноісторичних – ретроспективний, історико-генетичний та квантитативний, які обрані в межах локальної історії. Наукова новизна визначається відсутністю досліджень з
історичної юдаїки в межах Таврійської губернії в період революційних трасформацій 1917 р. А головним джерелом дослідження слугував щоденний сімферопольський часопис «Южные ведомости», у якому регулярно друкувалася інформація із зазначеної проблематики. Вперше висвітлюється ситуація в громадах Феодосії, Мелітополя, Євпаторії, Джанкоя, Генічеська та інших міст краю. Автор вводить
у науковий обіг значну частину інформації щодо самоорганізації єврейських громад Таврії, їхньої участі
в суспільно-політичному житті губернії, партійного будівництва. Вперше проаналізовано персональний склад списків під час муніципальної кампанії та підготовки виборів до Всеросійських Установчих
зборів, загалом їхні результати. Визначено головні дискусійні питання у середовищі єврейських громад
краю, політико-ідеологічні пріоритети діяльності соціалістів та сіоністів. Висновки Підсумовують
працю висновки про пріоритетну увагу єврейського населення Таврії до питань власної самоорганізації
та участі у виборах до органів міського самоврядування. Доведено, що революційні виклики супроводжувалися гострим протистоянням між сіоністами та соціалістами, які найчастіше не знаходили
порозуміння у ключових питаннях стратегії й тактики діяльності. При цьому більшою впливовістю
користувалися сіоністські структури. З’ясовано, що у переважній більшості випадків єврейські громадсько-політичні та партійні структури не ставали лідерами виборчих перегонів, отримуючи обмежену кількість думських мандатів. Research aim. The article examines the participation of Jewish communities in the Tavriya
province (except Simferopol) in the socio-political life of the region. The main source of the study was the
daily magazine “Yuzhnye Vedomosti”. It regularly published information on this issue. The author covers
the situation in the communities of Feodosia, Melitopol, Yevpatoria, Dzhankoi, Genichesk and other cities.
The research methodology is determined by choice as the main thing analyzed in general scientific methods,
in particular analytical and method of retrospective, historical-synthetic, description of general-historical
genetic and quantitative, which are selected in the framework of studies of local history. The scientific
novelty is determined by the lack of research on historical Judaism within the Tavriya province during the
revolutionary transformations of 1917. The author introduces into scientific circulation a significant part
of information about the self-organization of the Jewish communities of Tavria, their participation in the
socio-political life of the province, party building. For the first time, the personal composition of the lists
was analyzed during the municipal campaign and preparations for the elections to the All-Russian
Constituent Assembly, and their results in general. The main issues of discussion among the Jewish communities
of the region, political and ideological priorities of the socialists and Zionists have been identified.
Conclusions. The work is summed up by the conclusions that Feodosia was most often in the focus of the
publication’s attention, as evidenced by the total number of mentions in the pages of the magazine. According
to the author’s calculations, at least 43 times the newspaper’s journalists informed readers about
the events around the city’s Jewish community. According to this indicator, it was second only to the provincial
center. The peak months were April, May and June, when discussions on the most pressing issues of
community life reached their apogee. A sufficient number of posts and notes concerned the communities
of Melitopol and Yevpatoria.
According to published reports, the majority of local Jewish communities welcomed the news of the
fall of the Romanov monarchy. They expressed support for the new Russian government and hoped for
positive changes in the socio-political sphere. Priority topics for discussion at numerous meetings were
issues of internal self-organization, participation in elections to city councils and the All-Russian Constituent
Assembly, delegation of candidates to national congresses, and educational and charitable activities.
At the same time, two areas of controversy took a dominant place – the creation of institutions for
the management of community life and municipal elections.
We did not find any reflections of the communities of the region on the formation of the Ukrainian
Central Council, the General Secretariat, their confrontation with the Provisional Government of Russia,
the proclamation of the autonomy of Ukraine or the UPR in the pages of the magazine. Fragmentary and
often concise reports in the “Yuzhnye Vedomosti” do not allow to fully reveal the peculiarities of the Jewish
communities of the Tavriya province, but newspaper material is an important source for the matrix reconstruction
of those social transformations caused by the 1917 revolution.